Estudo sobre a prevenção do uso indevido de álcool e outras drogas em um Instituto Federal de Educação no estado de São Paulo - Silva, Debora Cavalcante Da [UNIFESP] (2020)
The use of alcohol and other drugs has affected countless people around the world, causing thousands of deaths each year, and can bring several other losses such as: disabilities, health consequences, dependence, etc. Data indicate that adolescents and young people are vulnerable to drug use and are more likely to put themselves at risk due to this use, with the need for preventive interventions in this regard, thus, the school becomes an important environment for carrying out actions with this audience. Thus, this study aimed to study, through an online questionnaire with servers, the prevention of the use of alcohol and other drugs in a “Federal Education Institute”, seeking to understand the prevalence, characteristics and types of existing actions in this sense, as well difficulties and obstacles to its implementation. To complement this study, an integrative review of experience reports on the prevention of the use of alcohol and other drugs in Brazilian schools was also carried out, with the objective of knowing how interventional actions are carried out in relation to drug use in schools. The results of the integrative review demonstrated that the vast majority of preventive interventions in the Brazilian school context were carried out in public educational institutions; more than half of the actions reached only one school/campus, among which there were some that were carried out only for a single room/class, or for a small number of students, not reaching the entire school; most of them were carried out through university extension projects, without the participation of parents, and without the active participation of teachers from the target schools (elementary and high school) in the activities carried out. In the study with professionals from the federal education institute, 63 civil servants from 28 campuses from the institution participated in the study, located in several cities in the State of São Paulo. The results showed that the prevention, when carried out, is done in the great majority of the times by means of occasional lectures and without regularity; 71.4% of employees said that their campus does not currently have a project or program to prevent the use of alcohol and other drugs, and another 27% have never heard of the existence of a project or program in place on their campus. The difficulties and obstacles encountered were: lack of training; doubts about how to act; feeling of not being properly prepared to act on this issue; lack of support from the school community (teachers, parents, administrative staff, community around the school) and lack of awareness on the subject of drugs; lack of institutional support; rare discussions and events on the subject within the school. Finally, we consider it necessary to carry out more scientific research on the subject, especially involving practices and experiences in the school context, and greater dissemination of scientific studies.